Efecto del índice de complejidad económica sobre la inversión extranjera directa en Ecuador durante el periodo 1990 – 2021, usando modelos de series de tiempo - Chuquimarca Pizarro, Leydi Tatiana (2025)
Although the attraction of Foreign Direct Investment (FDI) is essential for the economic development of countries, especially in developing countries, investment in Ecuador has been limited representing only 1% of the Gross Domestic Product and focused on low value-added sectors. This research evaluates the relationship between the economic complexity index and foreign direct investment in Ecuador during the period 1990 - 2021 with the objective of proposing mechanisms to strengthen the investment environment. An econometric analysis was carried out using a time series, with data from the World Bank and the Atlas of Economic Complexity. The methodology included unit root tests, cointegration analysis, autoregressive models, Error Correction Vector models and Granger causality tests. The results revealed a negative long-run relationship and the presence of bidirectional causality between the study variables. In view of this, strategies aimed at diversifying the productive structure of the country to attract foreign investment, through tax incentives, improvement of industrial park conditions and cooperation agreements with foreign companies that include the construction of joint innovation laboratories and technology transfer, are recommended.